Environmental audit behaviour, decision pattern, and market performance of small and medium enterprises in Nigeria - Eseroghene Franklin Udjo (African Journal of Environmental Economics and Management, 2013)
The environmental audit behaviour and decision making pattern of Nigerian SMEs is obscure. Given the fact that the Nigerian business environment is turbulent, the study finds out whether the decision making process of Nigerian SMEs is contingent upon information from the business environment. The study, utilizing correlation statistical procedure examines the subject of discourse. The results of the study suggest that the analysis of technological, customer and competitive factors have partial effect on the market share of Nigerian SMEs. Conversely, the analysis of socio-cultural factor of the Nigerian business environment has inverse effect on the market share of the SMEs. The study concludes that the environmental audit behaviour of Nigerian SMES have partial effect on market performance.